2019
DOI: 10.48550/arxiv.1907.01601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Derrida--Retaux conjecture on recursive models

Abstract: We are interested in the nearly supercritical regime in a family of max-type recursive models studied by Derrida and Retaux [7], and prove that under a suitable integrability assumption on the initial distribution, the free energy vanishes at the transition with an essential singularity with exponent 1 2 . This gives a weaker answer to a conjecture of Derrida and Retaux [7]. Other behaviours are obtained when the integrability condition is not satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…What the disordered critical behavior really is remains mathematically a fully open issue. Substantial progress on this problem has been recently achieved, but not for the pinning models itself: the critical behavior of a relevant disorder case for one class of copolymer pinning models and of a simplified version of the hierarchical pinning model have been identified respectively in [1] and in [9].…”
mentioning
confidence: 99%
“…What the disordered critical behavior really is remains mathematically a fully open issue. Substantial progress on this problem has been recently achieved, but not for the pinning models itself: the critical behavior of a relevant disorder case for one class of copolymer pinning models and of a simplified version of the hierarchical pinning model have been identified respectively in [1] and in [9].…”
mentioning
confidence: 99%
“…One of the main reason is that the model is expected to be in the strong or infinite disorder universality class [17,26,43], see also the more recent contribution [22]. In this line there have been also some mathematical progress [10,16], but they do not impact directly the pinning model.…”
Section: Exploiting the Legendre Transform And The Key Role Of The St...mentioning
confidence: 99%
“…Since then, a body of work with an increasing level of generality has emerged [67,28,37,9] ultimately considering critical conditioned Bienaymé-Galton-Watson tree (with finite variance) for the underlying tree and independent car arrivals whose laws may depend on the degree of the vertices [32]. See [10,29] for the case of supercritical trees. In this broad context, it was shown that a sharp phase transition appears for the parking process: there is a critical "density" of cars (depending on the combinatorial details of the model) such that below this density, almost all cars manage to park, whereas above this density, a positive proportion of cars do not find a parking spot.…”
Section: Introductionmentioning
confidence: 99%